Zukunftsermittlung im Barockdrama: von Träumen, Visionen und Prophezeiungen - Worms, Katharina (Daphnis, 2023)
Abstract This article deals with knowledge of the future in German drama of the 17th century. Within eight case studies the author focusses on scenes of predictions from Jacob Bidermanns Cenodoxus (1602, dt. 1635) to Christian Weises Marschall von Biron (1687). Open models of the future exist side by side with a deterministic understanding of time. However, also contemporary events play a role in the dramas, but they are not emphasized as present.